2017
DOI: 10.3126/jnps.v37i1.16301
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage Caused by Vitamin K Deficiency Beyond Neonatal Period

Abstract: Vitamin K deficiency bleeding (VKDB) can manifest as intracranial hemorrhage (ICH) and is still prevalent in poor resource countries. Infants aged one to twelve months with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
2
1
Order By: Relevance
“…The blood test results of all patients showed anemia and another previous study [14] revealed the same result. PRC transfusion can improve hemoglobin immediately to the normal range.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The blood test results of all patients showed anemia and another previous study [14] revealed the same result. PRC transfusion can improve hemoglobin immediately to the normal range.…”
Section: Discussionsupporting
confidence: 76%
“…The results of this study revealed GOS-ePed score of 80% of patients was between upper and lower good recovery, without death. It was better than other previous studies have reported [6,10,14,15]. The mortality rate was from 12 to 25%.…”
Section: Discussioncontrasting
confidence: 55%
“…This case series, with other report of VKDB in Nepal [27] , should be taken as an evidence of a cause specific occurrence of infant deaths which can be prevented through a simple and affordable intervention. The relatively low proportion (57.4%) of institutional delivery [2] would be a challenge to effectively deliver a birth dose injection of VK.…”
Section: Discussionmentioning
confidence: 63%
“…In countries without such national policy, like Nepal, only some children delivered in the private sector may get this affordable life-saving intervention, which is not equitable. A tertiary referral centre in Nepal identified 16 cases of ICH due to VKDB, of which only 3 (18.7%) had received VK at birth [27] . In current series, we could be certain about only one out of 16 (6%) infants of having received VK at birth.…”
Section: Discussionmentioning
confidence: 99%